Clinical, Colonoscopic and Histological profile of Abdominal Tuberculosis in BPKIHS, Nepal - Peeyush, Denis; Bajracharya, Sandeep Raj; Subedi, Prashant; Mandal, Rajesh Kumar; Sapkota, Prakash; Pradhan, Bickram (Journal of Advances in Internal Medicine, 2025)
BACKGROUND The diagnosis of abdominal tuberculosis is often challenging due to diverse and nonspecific clinical presentations. Abdominal Tuberculosis is not uncommon in developing countries like Nepal. The delay in diagnosis and treatment can lead to poor outcome in patients. Thus, this study aimed to evaluate the clinical, colonoscopic, and histopathological features of this condition in Nepal. METHODS This was a prospective observational study in which 44 patients with abdominal TB were analyzed for clinical, colonoscopic and histological profiles from June 2023 to May 2024. All diagnosed patients received Anti-tuberculosis Therapy (ATT) and were followed up at 2 and 6 months of ATT. RESULTS Among 44 patients 17 (38.63%) were male and 27 (61.36%) were female with mean of 39 years. The most common symptoms were anorexia (93.18%), abdominal pain (88.63%), weight loss (81.81%), abdominal distension (38.63%), diarrhoea (34.09%), fever 22.72% and vomiting (22.72%). Mantoux test was positive in 16 (36.36%) patients and 33 (75%) patients had elevated ESR. The sites involved were ileal in (70.45%), ileo-cecal (27.72%), peritoneal (20.45%), lymph nodal (18.18%) and colonic in (13.63%). TB PCR was positive in 6.81%. All patients had Lymphoid, histiocyte and plasma cell infiltration in histopathological examination. Caseating granuloma was seen in (11.36%). 41 out of 44 (93.18%) patients improved with Anti Tuberculosis Therapy (ATT). CONCLUSIONS The common symptoms of abdominal TB were anorexia, abdominal pain, weight loss, abdominal distension, chronic diarrhea and fever. Clinical features, imaging findings, ascitic ADA level along with histopathological reports should be considered for clinical diagnosis of abdominal TB. A therapeutic trial of ATT is indicated so that abdominal TB can be treated early in the course of disease.